Osteocalcin is associated with triglyceride glucose index rather than HOMA-IR in men with type 2 diabetes - Huang, Huijie; Wang, Ai; Cong, Li; Zeng, Yingjuan (Frontiers in Endocrinology, 2022)
Introduction The involvement of osteocalcin in the regulation of glucose tolerance in humans is controversial. We utilized a novel and practical insulin resistance surrogate, the triglyceride-glucose (TyG) index, to investigate the association between serum osteocalcin and insulin resistance in men with type 2 diabetes (T2D). Methods This was a retrospective cross-sectional study that included 667 male patients suffering from T2D, with measurements of N-terminal mid-fragment of osteocalcin (N-MID), triglycerides (TG), fasting blood glucose (FBG) and C-peptide collected on the same day. We used the TyG index and HOMA-IR as surrogate measures for insulin resistance. Binary logistic regression models that adjust the sociodemographic characteristics and metabolism-related factors were used to assess the associations between osteocalcin and insulin resistance. Restricted cubic spline (RCS) analysis was used to test the potential non-linear relationship between N-MID and the risk of severe insulin resistance. Subgroup analysis evaluated the robustness of the association. Results N-MID was correlated with the level of insulin resistance when quantified by the TyG index in unadjusted and adjusted binary logistic regression models (all p < 0.05), but the relationship was not observed when assessed by HOMA-IR (all p > 0.05). RCS model further confirmed that the association between N-MID and the severe insulin resistance measured by the TyG index was non-linear (P = 0.047). Subgroup analysis showed that the association was detected only in younger patients with lower BMI and poorer glycemic control, without hypertension or smoking. Conclusions Osteocalcin was inversely associated with the TyG index in men with T2D.